Penguatan Nilai-nilai Nasionalisme dalam Pembelajaran Sejarah Bagi Peserta Didik Kelas XI SMA Negeri 4 Kabupaten Sorong - Dominikus D Petun; Miftahuddin Miftahuddin (Indonesian Journal of Social Science Education (IJSSE), 2023)
The purpose of this study was to find out (1) The process of strengthening the values of nationalism in history learning (2) Understanding of nationalism by students of SMA Negeri 4 Sorong Regency (3) Obstacles found in strengthening nationalism values through learning History and the solutions. Researchers used qualitative research methods, with a descriptive approach. The research location is SMA Negeri 4 Sorong district. Data collection techniques using direct observation techniques, interviews, documentation and triangulation. The results showed that: (1) The process of strengthening nationalism values in history learning for class XI SMA Negeri 4 Sorong Regency, the history teacher had done well, namely: in the planning process, the process of implementing and evaluating in learning (2) Students as the next generation of the nation is increasingly aware of and optimistic and proud as part of the unitary state of the republic of Indonesia. Some of the values of nationalism that they understand include love for the motherland, unity and oneness, willingness to sacrifice, courage and discipline. The values of nationalism in historical learning are very important to be implemented for students through historical materials that are integrated with the values of nationalism (3) Obstacles encountered in strengthening the values of nationalism are curriculum competence, facilities and infrastructure and inadequate family environment support.